Finite Element Solution of the Contact Problem - Karabulut, Pembe Merve; Yaylacı, Murat; Birinci, Ahmet (Fırat University, 2018)
In this paper, continuous and discontinuous contact problems for an elastic layer loaded by symmetrical distributed loads whose lengths are 2a on an elastic semi-infinite plane is solved using finite element method. The elastic layer also subjected to uniform vertical body force because of effect of the gravity. Thickness in z direction is taken to be unit. It is assumed that the contact surfaces are frictionless, only normal tractions can be transmitted through the contact areas. The contact along the interface between elastic layer and half plane is continuous if the value of load factor is less than a critical value. In continuous and discontinuous contact cases, the stress distribution on the contact interface are plotted for different dimensionless quantities. The finite element model of the problem is constituted using ANSYS software and analysis of the problem is carried out. Finally, the results obtained from the finite element solution are verified by comprasion with the analytical results.
Keywords: Engineering; Mühendislik